ELECTION PARTICIPANTS' CAMPAIGN ON SOCIAL MEDIA DURING QUIET TIMES BASED ON KPU REGULATION NUMBER 232018 AND FIQH SIYASAH PERSPECTIVE - Mutia Khairani Hasibuan; Mhd. Yadi Harahap (PT. Radja Intercontinental Publishing, 2024)
The use of social media as a campaign method for election participants can be very effective in building wide contacts and saving time compared to other campaign methods. This shows that with the help of social media, politicians and political parties can easily campaign anywhere and at any time, meaning that campaigning on social media is not limited by location and time. However, as a candidate, this can be realized as a form of campaign.The aim of this research is to find out whether this should be considered an election violation or a form of freedom of expression. The use of social media for non-campaign activities must be seen from several different points of view, this activity is a form of election violation but can also be seen as a form of freedom of opinion. The campaign in fiqh siyasah is not yet familiar and widely known. The term predates contemporary times, when many Muslim-majority countries, especially in the Middle East and Southeast Asia, formed democratic nation-states. Campaign behavior is one of the main parts in organizing elections. In Siyasaah Fiqh the word for general elections is called Intikhabah Al-'Ammah, Intikhabah is Jama'muannas' salim which means to choose. This research will examine in more depth the use of social media by election participants during the quiet period in terms of general election commission regulation number 23 of 2018 and also fiqh siyasah by using the opinion of Yusuf Al Qardhawi with the concept or theory of Siyasah Al-Syarr'iyyah, namely in terms of campaign.